2007
DOI: 10.1007/s10854-007-9392-4
|View full text |Cite
|
Sign up to set email alerts
|

Phase formation and microstructure of Nd+3 doped Pb(Mg1/3Nb2/3)O3 prepared by sol–gel method

Abstract: The aim of this study was to investigate the effects of the rare earth element neodymium on the phase formation and microstructural development of relaxor ferroelectric lead magnesium niobate, Pb(Mg 1/3 Nb 2/3 )O 3 (PMN) system. Perovskite phase PMN powders were prepared using the sol-gel method and the effect of neodymium doping was investigated at different doping levels ranging from 0.1 mol% to 30 mol%. The precursors employed in the sol-gel process were lead (II) acetate, magnesium ethoxide, and niobium (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…No-vacancies are created for PGMN-R and hence the grain growth during sintering is not influenced. Similar grain size variations have been reported for rare-earths doped PMN and PMN-PT systems with similar doping level [38][39][40].…”
Section: Phase Analysis Using Xrd Edxs and Semsupporting
confidence: 84%
“…No-vacancies are created for PGMN-R and hence the grain growth during sintering is not influenced. Similar grain size variations have been reported for rare-earths doped PMN and PMN-PT systems with similar doping level [38][39][40].…”
Section: Phase Analysis Using Xrd Edxs and Semsupporting
confidence: 84%
“…In addition, it clearly showed that the peaks at 700 1C are optimum phase of perovskite PMN coating. A consideration of the structural variations accompanying the pyrochlore-perovskite transformation can give insight into how the relative permittivity might be changed from unit cell to unit cell [11,12].…”
Section: Resultsmentioning
confidence: 99%
“…Little is known, however, on the effect of milling time on the properties of PMN ceramics. Earlier work by the authors Chaipanich et al [10], Deliormanli et al [11][12][13], Beltran et al [14] has shown that an increase in the perovskite phase of PMN powder was found when the starting precursors such as MgNb 2 O 6 and PbO were subjected to longer milling [10]. Nevertheless, it is not known the effect of these powders on the properties of ceramics.…”
Section: Introductionmentioning
confidence: 99%